Life assessment of power transformers via paper ageing analysis - Zalizah Poniran, author; Zulkurnain Abdul Malek, author; International Conference on Power Engineering, Energy and Electrical Drives (2007: Portugal) (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL